Big data security analysis method based on self-update threat intelligence database - Yanfang HOU; Jinhua WANG (Dianxin kexue)
Big data security analysis method is generally based on the existing signature database to detect and match malicious behaviors.This method can only detect known attacks and can't analyze and judge new types of unknown attacks and complex variant attacks.Through the big data analysis technology,the collected data was extracted for safety value,and the value conversion from the collected data,threat information,threat knowledge to threat intelligence was realized,high-value threat intelligence of forming hidden,value selective,adversarial,predictive,and decision-making,evidence-based,time-sensitive was formed.Firstly,the limitations of the existing security analysis methods were analyzed.Then the construction method of threat intelligence database was introduced in detail.Finally,the security analysis method of big data based on self-renewing threat information database was described.The analysis of big data security based on the self-updated threat intelligence database could mine the hidden threats in internet data effectively and strengthen the existing security protection capabilities of internet companies so that the preemptive defense initiative could be mastered during the security game.